Infections Caused by Non-Tuberculous Mycobacteria in Recipients of Hematopoietic Stem Cell Transplantation - Al-Anazi, Khalid Ahmed (Front Oncol, 2014)
Non-tuberculous mycobacteria (NTM) are acid-fast bacteria that are ubiquitous in the environment and can colonize soil, dust particles, water sources, and food supplies. They are divided into rapidly growing mycobacteria such as Mycobacterium fortuitum, Mycobacterium chelonae, and Mycobacterium abscessus as well as slowly growing species such as Mycobacterium avium, Mycobacterium kansasii, and Mycobacterium marinum. About 160 different species, which can cause community acquired and health care-associated infections, have been identified. NTM are becoming increasingly recognized in recipients of hematopoietic stem cell transplantation (HSCT) with incidence rates ranging between 0.4 and 10%. These infections are 50–600 times commoner in transplant recipients than in the general population and the time of onset ranges from day 31 to day 1055 post-transplant. They have been reported following various forms of HSCT. Several risk factors predispose to NTM infections in recipients of stem cell transplantation and these are related to the underlying medical condition and its treatment, the pre-transplant conditioning therapies as well as the transplant procedure and its complications. Clinically, NTM may present with: unexplained fever, lymphadenopathy, osteomyelitis, soft tissue and skin infections, central venous catheter infections, bacteremia, lung, and gastrointestinal tract involvement. However, disseminated infections are commonly encountered in severely immunocompromised individuals and bloodstream infections are almost always associated with catheter-related infections. It is usually difficult to differentiate colonization from true infection, thus, the threshold for starting therapy remains undetermined. Respiratory specimens such as sputum, pleural fluid, and bronchoalveolar lavage in addition to cultures of blood, bone, skin, and soft tissues are essential diagnostically. Susceptibility testing of mycobacterial isolates is a basic component of optimal care. Currently, there are no guidelines for the treatment of NTM infections in recipients of stem cell transplantation, but such infections have been successfully treated with surgical debridement, removal of infected or colonized indwelling intravascular devices, and administration of various combinations of antimicrobials. Monotherapy can be associated with development of drug resistance due to new genetic mutation. The accepted duration of treatment is 9 months in allogeneic stem cell transplantation and 6 months in autologous setting. Unfortunately, eradication of NTM infections may be impossible and their treatment is often complicated by adverse effects and interactions with other transplant-related medication.